Usaha Mendapatkan Pengakuan Internasional: Kebijakan Indonesia Mengeluarkan Peraturan Presiden 125/2016 dalam Menangani Isu Pengungsi - Sirait, Kevin Ronaldo; Rosyidin, Mohamad; Putranti, Ika Riswanti; Charlotte, Shary (Universitas Diponegoro, 2019)
As a transit country, Indonesia is obliged to temporarily accommodate thousands of refugees and asylum seekers who are waiting to be processed by UNHCR for resettlement to the third countries. To facilitate refugees and asylum seekers, Joko Widodo’s government issued Presidential Regulation 125/2016. The international community appreciates the regulation because it shows Indonesia commitment to take part in addressing one of the humanitarian issues that is currently being concern to the world. This paper aims to analyze Joko Widodo’s policy that facilitate refugees and asylum seekers. By using the concept of international recognition in the constructivist paradigm, this paper argues that the government issued Presidential Regulation 125/2016 is influenced by the desire of Indonesia to be recognized as a “human rights defender” in terms of refugee handling. In this case, recognition, appreciation, and positive response from the international community has been obtained by Indonesia leading to the reduction of pressure from international community which could trigger the phenomenon of misrecognition. In this regard, Indonesia’s identity as “human rights defender” can be maintained.